PGPR for the management of sunflower major diseases of north eastern dry zone of Karnataka: PGPR for the management of sunflower major diseases of north eastern dry zone of Karnataka - T POORNIMA,; VIKAS V KULKARNI,; VIJAYAKUMAR GHANTE,; M R UMESH, (Journal of Oilseeds Research, 2020)
Field experiment was conducted during rabi 2017-18 and kharif 2018 to study the effect of PGPR (plant growthpromoting rhizobacteria) on sunflower diseases. Among treatments, seed treatment with Pseudomonas fluorescens @ 10g/kg seed + soil application of 2.5 kg P. fluorescens @ 2.5 kg fortified with 250 kg FYM + three foliar spray of P. fluorescens @ 30, 45 and 60 DAS had recorded least PDI of Alternaria leaf spot (28.9%), powdery mildew (28.8%) and percent disease incidence of necrosis (24) with highest yield of 1612 kg/ha compared to other treatments.